2011
DOI: 10.1063/1.3655328
|View full text |Cite
|
Sign up to set email alerts
|

Complex Bragg grating writing using direct modulation of the optical fiber with flexural waves

Abstract: A flexural wave is applied to an optical fiber during the process of Bragg grating inscription using the direct writing method through a phase mask. Using this approach, we can dither the writing process to allow complex grating writing. Examples we demonstrate are tunable sampled gratings and phase-shifted gratings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
(13 reference statements)
0
13
0
Order By: Relevance
“…Supposing T A and T B represents the factor of primary and secondary transmission deep separately, then the range of T A /T B can be calculated as 0.18-1.80, 0.06-2.83 and 3.91 10 4 × − -32. 22, respectively. When the modulation depth of FBG-AOTF refractive index changes, the range of T A /T B will be different.…”
Section: Characteristic Description Of the Fbg-aotfmentioning
confidence: 95%
See 1 more Smart Citation
“…Supposing T A and T B represents the factor of primary and secondary transmission deep separately, then the range of T A /T B can be calculated as 0.18-1.80, 0.06-2.83 and 3.91 10 4 × − -32. 22, respectively. When the modulation depth of FBG-AOTF refractive index changes, the range of T A /T B will be different.…”
Section: Characteristic Description Of the Fbg-aotfmentioning
confidence: 95%
“…Since a fiber Bragg grating based AOTF (FBG-AOTF) which is also named as FBG based acousto-optic superlative modulator has been proposed by Liu et al [12], the research in the FBG-AOTF has observed a great development [13][14][15][16][17][18][19]. Because the spectral and wavelength can be controlled by the acoustic wave (AW), the FBG-AOTF can be widely applied in add-drop multiplexer [20], fiber laser [21], and grating writing [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the effect of applying an acoustic flexural wave longitudinally to an optical fiber during the process of Bragg grating inscription using the direct writing method through a phase mask was demonstrated and showed that it can be used to obtain precise control over the grating parameters in order to achieve sampled gratings and phase-shifted gratings [12]. However, regarding the generation of cavities for phase shift, only preliminary results have been presented.…”
Section: Introductionmentioning
confidence: 98%
“…This technique has made possible the development of a vast range of devices, such as distributed feedback fiber lasers [2,3], optical narrowband filters [4], optical code division multiple access en/decoders [5,6], multiplexers/demultiplexers [7] and so on, that are based on, for example, phase-shifted gratings [8] and sampled gratings [9][10][11]. In this paper, we present a modified methodology previously demonstrated in [12], where a direct acoustic modulation of the fiber is used, however using only the set of the acoustic burst time characteristics.…”
Section: Introductionmentioning
confidence: 98%
“…It has been successfully applied in the design and construction of various low insertion loss all-fibre devices such as a tunable dispersion compensator, tunable optical notch filter [6,7] and complex Bragg grating writing [8], among others. Also, using a LPG, a viscosity and density sensor was reported [9].…”
Section: Introductionmentioning
confidence: 99%